Faecal microbiota signatures of IBD and their relation to diagnosis, disease phenotype, inflammation, treatment escalation and anti-TNF response in a European Multicentre Study (IBD-Character). (2nd October 2020) - Vatn, S.; Carstens, A.; Kristoffersen, A. B.; Bergemalm, D.; Casén, C.; Moen, A. E. F.; Tannaes, T. M.; Lindstrøm, J.; Detlie, T. E.; Olbjørn, C.; Lindquist, C. M.; Söderholm, J. D.; et al.
Abstract: Method: We examined faecal samples, using the GA-map™ Dysbiosis Test, to associate gut microbiota composition with Crohn's disease (CD) and ulcerative colitis (UC) and to identify markers for future biomarker identification. We conducted a prospective case-control study (EU-ref. no. 305676) in an inception cohort of 324 individuals (64 CD, 84 UC, 116 symptomatic non-IBD controls and 44 healthy controls) across five European centres and examined 54 predetermined bacterial markers. We categorized patients according to the Montreal Classification and calculated the dysbiosis index (DI). Non-parametric tests were used to compare groups and the Bonferroni correction to adjust for multiple comparisons. Results: The fluorescent signals (FSSs) for Firmicutes and Eubacterium hallii were lower in inflammatory bowel disease (IBD) vs. symptomatic controls ( p <.05). FSS for Firmicutes, Lachnospiraceae, Eubacterium hallii and Ruminococcus albus/bromii were lower, whereas the signal for Bacteroides Fragilis was higher in UC vs. symptomatic controls ( p <.05). FSS was higher for Bifidobacterium spp., Eubacterium hallii, Actinobacteria and Firmicutes among patients with ulcerative proctitis, compared to extensive colitis ( p <.05). In CD, we observed no association with disease location. The DI correlated with faecal-calprotectin in both CD and in UC ( p <.001). In terms of treatment escalation and anti-TNF response, differences were observed for some bacterial markers, but none of these associations were statistically significant. Conclusion: Our data reveal that the GA-map™ Dysbiosis Test holds the potential to characterize the faecal microbiota composition and to assess the degree of dysbiosis in new-onset IBD. On the other hand, our results cannot demonstrate any proven diagnostic or predictive value of this method to support clinical decision making.